After the RCT: who comes to a family-based intervention for childhood overweight or obesity when it is implemented at scale in the community?. Issue 2 (7th October 2014) - Fagg, James; Cole, Tim J; Cummins, Steven; Goldstein, Harvey; Morris, Stephen; Radley, Duncan; Sacher, Paul; Law, Catherine
Abstract : Background: When implemented at scale, the impact on health and health inequalities of public health interventions depends on who receives them in addition to intervention effectiveness. Methods: The MEND 7–13 (Mind, Exercise, Nutrition…Do it!) programme is a family-based weight management intervention for childhood overweight and obesity implemented at scale in the community. We compare the characteristics of children referred to the MEND programme (N=18 289 referred to 1940 programmes) with those of the population eligible for the intervention, and assess what predicts completion of the intervention. Results: Compared to the MEND-eligible population, proportionally more children who started MEND were: obese rather than overweight excluding obese; girls; Asian; from families with a lone parent; living in less favourable socioeconomic circumstances; and living in urban rather than rural or suburban areas. Having started the programme, children were relatively less likely to complete it if they: reported 'abnormal' compared to 'normal' levels of psychological distress; were boys; were from lone parent families; lived in less favourable socioeconomic circumstances; and had participated in a relatively large MEND programme group; or where managers had run more programmes. Conclusions: The provision and/or uptake of MEND did not appear to compromise and, if anything, promoted participation of those from disadvantaged circumstances and ethnic minority groups. However, this tendency was diminished because programme completion was less likely for those living in less favourable socioeconomic circumstances. Further research should explore how completion rates of this intervention could be improved for particular groups.